Cumulated Lawsuit And Tort: Legal Reasoning of Judges and Major Decision’s Ratio Decidendi (Study of Supreme Court Decision No. 575 K/Pdt/1983 and Supreme Court Decision No. 2686/Pdt/1985) - Aries Isnandar; Vanka Lyandova; Yogi Prasetyo; Ferry Irawan Febriansyah; Alfalachu Indiantoro; Ucuk Agiyanto (Jurnal Jurisprudence, 2022)
ABSTRACT Purpose of Study: This research aimed at analyzing Supreme Court Decision No. 575 K/Pdt/1983 and Supreme Court Decision No. 2686/Pdt/1985 concerning cumulative lawsuits and tort according to the judge's legal reasoning.  Methodology: This is library research using the normative juridical method. The approach used was the statutory approach. The statutory approach was carried out by analyzing Supreme Court Decision No. 575 K/Pdt/1983 and Supreme Court Decision No. 2686/Pdt/1985 in the context of the cumulative lawsuit and tort section. Result: This research found that even though unlawful acts and contracts are conventionally separated, there are still issues regarding overlapping understandings of the concepts of tort, cumulative lawsuit, and default in law. For example, there is an act by one party that, on the one hand, can be classified as an unlawful act, but it also has a contractual element. Similarly, one party’s actions have contractual consequences for the other party, but they can also result in liability based on tort. This condition causes several parties to accumulate lawsuits for unlawful acts and defaults at the same time. Supreme Court accepted the cumulative lawsuit in decision No. 575 K/Pdt/1983 and Supreme Court Decision No. 2686/Pdt/1985, indicating that it does not violate procedural law. Applications of this study:  This research is useful for analyzing Supreme Court Decision No. 575 K/Pdt/1983 and Supreme Court Decision No. 2686/Pdt/1985. These Supreme Court decisions have a ratio decidendi or jurisprudence that a cumulative lawsuit is permitted and it does not violate procedural law. Novelty: There are no previous researchers who conducted a legal analysis of the Supreme Court's decision, even though the Supreme Court is the jurisprudence in cases or legal issues of cumulative lawsuits and tort.   Keywords: Cumulation, Against the Law, Default, Decision, Ratio Decidendi  ABSTRAK  Tujuan: Penelitian ini bertujuan untuk menganalisis Putusan Mahkamah Agung No. 575 K/Pdt/1983 dan Putusan Mahkamah Agung No. 2686/Pdt/1985 tentang gugatan kumulatif dan perbuatan melawan hukum menurut penalaran hukum hakim.  Metodologi: Penelitian kepustakaan ini menggunakan metode yuridis normatif. Pendekatan yang digunakan adalah pendekatan Perundang-undangan. Pendekatan perundang-undangan dilakukan dengan menganalisis Putusan MA No. 575 K/Pdt/1983 dan Putusan MA No. 2686/Pdt/1985 dalam konteks gugatan kumulatif dan pasal perbuatan melawan hukum.  Hasil: Penelitian ini menemukan bahwa meskipun perbuatan melawan hukum dan perjanjian dipisahkan secara konvensional, masih terdapat permasalahan mengenai tumpang tindih pemahaman tentang konsep gugatan, gugatan kumulatif, dan wanprestasi dalam hukum. Misalnya, ada perbuatan salah satu pihak yang di satu pihak dapat digolongkan sebagai perbuatan melawan hukum, tetapi juga mengandung unsur perjanjian. Demikian pula, tindakan satu pihak memiliki konsekuensi kontraktual bagi pihak lain, tetapi tindakan tersebut juga dapat mengakibatkan pertanggungjawaban berdasarkan kesalahan. Kondisi ini menyebabkan beberapa pihak menumpuk tuntutan atas perbuatan melawan hukum dan wanprestasi secara bersamaan. Mahkamah Agung menerima gugatan kumulatif dalam putusan No. 575 K/Pdt/1983 dan Putusan MA No. 2686/Pdt/1985, yang berarti tidak melanggar hukum acara.  Aplikasi penelitian ini: Penelitian ini berguna untuk menganalisis Putusan Mahkamah Agung No. 575 K/Pdt/1983 dan Putusan Mahkamah Agung No. 2686/Pdt/1985. Putusan Mahkamah Agung ini memiliki ratio decidendi atau yurisprudensi bahwa gugatan kumulatif diperbolehkan dan tidak melanggar hukum acara.  Kebaruan/Orisinalitas: Belum ada peneliti terdahulu yang melakukan analisis hukum terhadap putusan MA, padahal MA merupakan yurisprudensi dalam perkara atau permasalahan hukum kumulatif gugatan dan perbuatan melawan hukum. Kata kunci: Kumulasi, Melawan Hukum, Wanprestasi, Putusan, Rasio Decidendi